Proceso atención de enfermería en neonato a termino con dificultad respiratoria leve y pie equinovaro bilateral. - Márquez Villacis, Celena Jamilex (2022)
The present study was carried out in a full-term male neonate with respiratory distress plus bilateral clubfoot. Respiratory distress is a respiratory condition that almost exclusively affects preterm infants, since lung maturation has not yet been completed in these immature children. There are pulmonary and extrapulmonary cause, among which extrapulmonary causes are the most frequent that affect term newborns. Clubfoot varo, also known as clubfoot, is a congenital condition in the which the foot is equine (pionted) and varus (plant turned inward), which is more common in boys than in girls. Various factors that affect this disease such as family history, genetic factors and insufficient amniotic fluid during pregnancy.